Analysis of roping of aluminum sheet materials based on the meso-scale moving window approach. (1st February 2015) - Qin, L.; Seefeldt, M.; Van Houtte, P.
Abstract: The moving-window method, on which a meso-scale roping model is based, is proposed to bridge the spatial gap between the grain-scale of the individual orientations and the macro-scale of the surface roping. The mesoscopic roping model is applied to numerically analyze the roping propensity in an AA6016 aluminum metal sheet under uniaxial tensile testing. The measured electron backscatter diffraction (EBSD) data are directly incorporated into the meso-scale roping model, in which the full constraints Taylor polycrystal plasticity model is used to simulate the r -value and then the thickness change for each window. The roping wavelength and amplitude are sought by assuming that roping is caused by the existence of mesoscopic volumes with contrasting textures. The simulated surface profiles are compared quantitatively with experimental measurements. The effect of the window size is discussed.